2018
DOI: 10.1111/liv.13655
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes of paediatric liver transplant recipients after transition to Adult Healthcare Service

Abstract: Adolescent LT patients who undergo transition to the AHS have good long-term outcomes. However, a multidisciplinary approach aiming at fostering adherence should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Health-care professionals in adult services have the potential to encounter treatment-related complications soon after transition compared to chronic liver diseases of adult-onset. 14 Within this cohort, a significant number of patients had already experienced transplant-related complications, two of these requiring a second transplant. Burra et al suggested that younger age at transplant is associated with increased risk of graft loss and that paediatric transplant recipients are more likely to experience immunosuppressantrelated renal dysfunction necessitating a kidney transplant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Health-care professionals in adult services have the potential to encounter treatment-related complications soon after transition compared to chronic liver diseases of adult-onset. 14 Within this cohort, a significant number of patients had already experienced transplant-related complications, two of these requiring a second transplant. Burra et al suggested that younger age at transplant is associated with increased risk of graft loss and that paediatric transplant recipients are more likely to experience immunosuppressantrelated renal dysfunction necessitating a kidney transplant.…”
Section: Discussionmentioning
confidence: 97%
“…15 Similarly, Ferrarese et al showed that chronic rejection and nonadherence were prevalent (18% and 25%, respectively). 14 However, overall, it is reassuring that children transitioning to adult services have been demonstrated to have reasonable long-term outcome with one study showing 10-year graft survival of 86%. 16 Structured transition to adult services is now being seen as a crucial process and normal standard of care in patients with chronic disease, 17,18 with guidance in the field of chronic liver disease having only recently being published.…”
Section: Discussionmentioning
confidence: 99%
“…The feeling of being different was considered to be one of the likely causes of non-adherent behavior by all the HCPs in the study which is in line with other studies exploring young people's experiences of life with a liver transplant. 25,26 Understanding barriers to adherence from the perspective of the young person is imperative for all professionals caring for this age group 27,28 In a rheumatology study of decision-making regarding biologic therapies for arthritis, young adults expressed the need for professionals to address the wider psychosocial impact of medication regimens and not just consider them in the context of disease control and the consequences of non-adherence. 29 Approaching adherence in a developmentally appropriate manner is imperative for success and yet is not always acknowledged by HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradictory results relating to graft loss following transfer to adult services 19 . Some studies demonstrate higher incidence of graft loss following transfer for LTRs 18 and similarly for renal transplant patients 20 ; however, others report no increase in graft loss following transfer for both LTRs and renal transplant patients 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…19 Some studies demonstrate higher incidence of graft loss following transfer for LTRs 18 and similarly for renal transplant patients 20 ; however, others report no increase in graft loss following transfer for both LTRs and renal transplant patients. 21,22 Evidence suggests that a structured transition process contributes to increased patient satisfaction, 23 quality of life, 24 coping, and symptom management. 25 Transition interventions for solid-organ transplant patients typically stem from pediatric services as demonstrated in a Canadian study where pediatric nurses were deemed to be best placed to initiate transition discussions with solid-organ transplant patients from the age of 14.…”
Section: Introductionmentioning
confidence: 99%